Eccentric training vs muscle energy technique in adjunct to low-level laser therapy for lateral epicondylitis - Sumedha, Govindaswamy; Gurudut, Peeyoosha; Welling, Aarti (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Low-level laser therapy (LLLT) is considered a mainstay intervention for lateral epicondylitis (LE) with clear evidence. Eccentric Exercises (EE) and Muscle Energy Technique [MET] have been shown to be beneﬁcial individually. However, trials are lacking where the above two approaches are compared. Further, no comprehensive EE protocol exists for LE. Hence, this study aimed to develop an EE protocol and evaluate the eﬀectiveness of the EE protocol versus MET as adjuncts to LLLT for the management of LE.Methods. A total of 34 (n = 17 in each group) participants with LE were randomly allocated to two study groups (EE and MET). The participants received either EE or MET along with LLLT as a common intervention over 3 weeks. The outcomes measured were pinch strength, grip strength, and pain pressure threshold, assessed at pre-intervention and post-intervention (3rd week). The patient-rated tennis elbow evaluation (PRTEE) questionnaire was assessed at 4 points in time: pre- and post-3 weeks with follow-up in the 6th week and 12th week.Results. When compared between the groups, a statistically signiﬁcant diﬀerence was noted with the EE group being more eﬀective than the MET group for pain pressure threshold (p = 0.001), key pinch strength (p = 0.003), tripod pinch strength (p = 0.107), grip strength (p = 0.046), pain and functional disability (p = 0.001).Conclusions. Although both EE and MET were eﬀective in treating lateral epicondylitis, eccentric exercises were superior to the MET group even at the 6th and 12th week follow-up, suggesting a longer-lasting eﬀect of EE without recurrences.
Keywords: lateral epicondylitis; low-level laser therapy; manual therapy; exercise therapy